(untitled) (Revista Contexto & Educação, 2024)
The present study addresses the issue of Autistic Spectrum Disorder (ASD) at the University, on the implications of the invisibility of the person with ASD and of ableism for existential dignity, in the teaching-learning process. Performed through a systematic review of indirect data available in scientific publications, the article structures the subject in three units. The first develops the characterization of the university as a space for coexistence. The second deals specifically with Autism Spectrum Disorder and the social invisibility that accompanies it. Finally, considering the reality of the teaching-learning process, the text confronts the concepts of ableism and dignified coexistence. Among other aspects, the study indicates that, from pedagogical practices to evaluation instruments, teaching-learning demands new approaches considering the scenario of neurodiversity’s. Higher education institutions are faced with the challenge of providing training content, in a social reality guided by guarantees that, among other aspects, recognize in individuality the assumption of respect for differences. In this context, ableism represents a concept related to attitudinal barriers that compromise the existential dignity of people with ASD, a fact whose effective transformation involves the production of spaces for open and other dialogue, as well as the recognition of the positive value of differences.